Synergistic effect of Si concentration and distribution on ferroelectric properties optimization of Si:HfO2 ferroelectric thin films. (12th October 2022) - Shao, Yanping; Yang, Wanting; Wang, Yuanyao; Deng, Yuhui; Liao, Ningtao; Zhu, Bingyan; Lin, Xin; Jiang, Limei; Jiang, Jie; Yang, Qiong; Zhong, Xiangli
Abstract: In this paper, a phase-field model of Si-doped hafnium oxide-based ferroelectric thin films is established. And then, the synergistic effect of Si concentration and distribution on ferroelectric properties optimization of Si:HfO2 ferroelectric thin films is studied with the proposed model. It is found that no matter how Si dopant is distributed in the film, the volume fraction of the ferroelectric phase in the film increases first and then decreases with the increase of Si concentration. However, compared with the uniform distribution, the layered distribution is more likely to great improve ferrelectric properties. When Si dopant is uniformly distributed in the film, the highest remanent polarization value that the film can obtain via Si concentration modulation is 38.7 μ C cm −2, and the corresponding Si concentration is 3.8 cat%, which is consistent with the experimental results. When Si dopant is layered in the film, and the concentration difference between the Si-rich and Si-poor layers is 7.6%, in the Si concentration range of 3.6 cat%–3.8 cat%, the residual polarization of the film reaches 46.4–46.8 μ C cm −2, which is 20% higher than that when Si dopant are evenly distributed in the film. The above results show that selecting the Si layered distribution mode and controlling the concentration difference between Si-rich and Si-poor layers in an appropriate range can greatly improve the films' ferroelectric properties and broaden the Si concentration optimization range of the ferroelectric properties of the films. The result provides further theoretical guidance on using Si doping to adjust the ferroelectric properties of hafnium oxide-based films.